Diffusion-weighted MR imaging in pancreatic ductal adenocarcinoma: prediction of next-generation sequencing-based tumor cellularity and prognosis after surgical resection - Jeon, Sun Kyung; Jang, Jin Young; Kwon, Wooil; Kim, Hongbeom; Han, Youngmin; Kim, Daeun; Park, Daechan; Kim, Jung Hoon (Abdominal Radiology, 2021)
Purpose: To identify features on preoperative MR imaging with diffusion-weighted imaging (DWI) for predicting next-generation sequencing (NGS)-based tumor cellularity and patient outcome after surgical resection of pancreatic ductal adenocarcinoma (PDAC). Methods: This retrospective study included 105 patients with surgically resected PDAC who underwent preoperative MR imaging with DWI. Tumor cellularity was measured using molecular techniques and bioinformatics methods. Clinico-pathologic findings including tumor T stage for predicting disease-free survival (DFS) and overall survival (OS) were identified using Cox proportional hazards model. Important MR imaging findings including apparent diffusion coefficient (ADC) value of PDAC and modified ADC value (the ratio of the ADC value of PDAC to the ADC value of the spleen) for predicting higher tumor cellularity (≥ 30%) and poor prognosis were also identified. Results: The median DFS and OS were 12.0 months [95% confidence interval (CI), 8.0–17.0] and 22.0 months (95% CI, 18.0–29.0), respectively. Higher T stage (T3/4) [hazard ratio (HR), 7.720, (95% CI 1.072, 55.612); p = 0.048] and higher tumor cellularity [HR, 1.599 (95% CI, 1.003–2.548); p = 0.048] were significantly associated with worse DFS. Among MR imaging features, the modified ADC value was significantly associated with tumor cellularity [odds ratio, 0.068 (95% CI, 0.012–0.372); p = 0.002], and PDAC with lower modified ADC value [≤ 1.40 (cutoff value)] showed significantly shorter median DFS than PDAC with higher modified ADC value [8 months (95% CI, 4–12) vs. 16 months (95% CI, 10–29); HR, 1.713 (95% CI, 1.073–2.735), log-rank p = 0.024]. Conclusion: Higher NGS-based tumor cellularity may be a negative prognostic factor in pancreatic cancer after resection, and modified ADC value derived from DWI could be helpful in predicting tumor cellularity and patient surgical outcome with regard to recurrence. Graphic abstract: [Figure not available: see fulltext.].
Keywords: Carcinoma, Pancreatic Ductal; Diffusion Magnetic Resonance Imaging; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Neoplasm Recurrence, Local; Pancreatic Neoplasms; Prognosis; Retrospective Studies; Magnetic resonance imaging; Pancreatic neoplasms; Prognosis; Recurrence